(3GdJfHD GdESJQGJjLjs - (3EHQGgje(B, (3GdSjOs ((3GdEScfOQjI(B:s (3OGQ GdJYdje GdLGeYj(B,s, 2017)
(3JfGhd gPG GdcJGH ehVhY GdJfHD GdGSJQGJjLj, MjK JWQb ef NdGd aUhdg Edi CSGSjGJ GdEOGQI GdGSJQGJjLjI hGdJNWjW GdGSJQGJjLj, HGdEVGaI Gdi GdEOGQI GdGSJQGJjLjI aj GdCLgRI GdMchejI, hGdNWhW GdJhLjgjI GdWhYjI GdeJYdbI HJbjje GdJCKjQGJ GdHjFjI GdNGU HGdJfhY GdHjhdhLj, ceG JMOK Yf CKQ GdMUI GdShbjI ddTQcI heYOd feh GdShb Ydi GNJjGQ GdHOjd GdGSJQGJjLj GdefGSH , hGdJYGhf GdJcfhdhLj hGfOeGL GdeDSSGJ, hCNjQG GdJfHD HGdeHjYGJ haYGdjI THcGJ GdEeOGO(B.s
(3HHdjhZQGajG U(B.285s
Keywords: (3GdEOGQI GdGSJQGJjLjIs; (3GdJNWjW GdESJQGJjLjs; (3GdJfHD GdESJQGJjLjs